RESPONSIBLE CONSUMPTION AND PRODUCTION: PROMOTING SUSTAINABLE PRACTICES IN UZBEKISTAN - Shoh-Jаkhon Khаmdаmov (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This paper examines the importance of responsible consumption and production in promoting sustainable development in Uzbekistan. It highlights the challenges and opportunities associated with adopting sustainable practices, such as reducing waste, improving resource efficiency, and promoting sustainable business models. The paper discusses various strategies and policies that can be implemented to foster responsible consumption and production, including regulatory measures, public awareness campaigns, and incentives for sustainable practices. By adopting these strategies, Uzbekistan can enhance environmental sustainability, support economic growth, and improve the quality of life for its citizens.